An entrained flow biomass gasification technology with the fluidized bed concept for low-carbon fuel production - Keigo Matsumoto (Applications in Energy and Combustion Science)
For accomplishing the vision of building of a net-emission zero society, low-carbon fuels such as e-fuel, Sustainable Aviation Fuel (SAF), and chemical products generation, plays a significant role. Especially, among the low carbon fuels, SAF is the most crucial. Ammonia and electric aircraft are under way as alternatives to fossil-derived jet fuel (kerosene). However, none of these have yet found their way to commercialization. Among the SAF production technology, biomass gasification and Fischer-Tropsch (FT) synthesis technology are one of the lowest CO2 emission processes, according to Life Cycle Assessment (LCA) analysis. However, at present there are some issues about biomass grinding, tar, ash treatment, gas purification and wastewater. We, at Mitsubishi Heavy Industries (MHI) R&D laboratory have developed entrained bed gasification, adopting the fluidized bed concept in which biomass particles are recirculated in the gasifier without fluidizer. Principally desired outcomes of this development was to reduce the grinding power, simplify the structure by using atmospheric pressure process, and lower tar concentration while maintain suitable temperature to prevent ash from melting inside gasifier. Empirical and actual results showed that the developed gasifier can obtain high carbon conversion ratio and low tar as compared to the traditional gasification processes for low-carbon fuel production and produce reliably stable syngas for low-carbon fuel synthesis with single gasifier. Based on the pilot plant operation results, effectiveness of moderate (1223 – 1323 K) temperature gasification with this concept has been demonstrated too. As a conclusion, development needs and expectation of gasification technology for contributing to carbon neutral society are mentioned.